Analisis Motivasi dalam Meningkatkan Produktivitas Kerja Karyawan di CV. Sumber Jaya Springs - Arsa Reynal Dimas Suyanto; Ari Susanto (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the impact of motivation on employee productivity at CV. Sumber Jaya Springs. The research method used is descriptive qualitative with a case study approach. Data were collected through in-depth interviews, participatory observation, and document studies. The results show that both external and internal motivation have a significant impact on employee productivity. Financial incentives such as bonuses and allowances, as well as recognition and appreciation from management, are proven effective in increasing employee motivation. Additionally, supportive leadership styles and conducive work environments also play important roles in enhancing work productivity. This study provides new insights and practical recommendations for companies in their efforts to improve employee productivity through effective motivation management.